2018
DOI: 10.1080/19476337.2017.1422278
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial pectin-gellan films: effects on three foodborne pathogens in a meat medium, and selected physical-mechanical properties

Abstract: It is first reported the elaboration and characterization of films (F2) containing 1% (w/v) citrus pectin, 0.2% (w/v) gellan gum, 0.5% (w/v) glycerol, CaCl 2 5 mM, ethylenediaminetetraacetic acid (EDTA) 0.05 M and 90 (Arbitrary Units)/mL of an antimicrobial concentrated supernatant (ACS) from fermentation culture broths of the lactic acid bacterium, Streptococcus infantarius. The functional films inhibited the growth of Listeria monocytogenes, Escherichia coli and Staphylococcus aureus in "Barbacoa" medium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Briefly, maintaining constant concentrations of 0.1% (w/v) CP (GENU® Pectin, DE = 36%, CP‐Kelco, USA) and 0.05% (w/v) low acyl GG (Kelcogel, CP‐Kelco, USA), combinations of AS (50 and 75 AU/ml) and EDTA (1, 4, and 8 mM) were tested for the antibacterial activity against E. coli , S. aureus, and L. monocytogenes in BHI, with initial concentrations of 1 × 10 5 CFU per well. The AS and EDTA concentrations were proposed based on previous reports (Jiménez‐Villeda et al., 2019; Trejo‐González et al., 2018). The plates were incubated at 35°C, reading the absorbance (545–630 nm) at 0, 20, 22, and 24 hr in a Stat Fax 2,100 equipment, Awerness Technology Inc. Three independent experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, maintaining constant concentrations of 0.1% (w/v) CP (GENU® Pectin, DE = 36%, CP‐Kelco, USA) and 0.05% (w/v) low acyl GG (Kelcogel, CP‐Kelco, USA), combinations of AS (50 and 75 AU/ml) and EDTA (1, 4, and 8 mM) were tested for the antibacterial activity against E. coli , S. aureus, and L. monocytogenes in BHI, with initial concentrations of 1 × 10 5 CFU per well. The AS and EDTA concentrations were proposed based on previous reports (Jiménez‐Villeda et al., 2019; Trejo‐González et al., 2018). The plates were incubated at 35°C, reading the absorbance (545–630 nm) at 0, 20, 22, and 24 hr in a Stat Fax 2,100 equipment, Awerness Technology Inc. Three independent experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Catimor) is a promising source of low methoxyl pectin. Unlike the antimicrobial properties of pectin from the previous study, which used pectin as a carrier for antimicrobial agents such as silver nanoparticles or essential oils [8,9,18,19], this type of pectin can be used in the biomedical or pharmaceutical fields without structure modification. The boiling extraction method seems to be the most appropriate for largescale extraction, as it yielded the highest amount of pectin.…”
Section: Antibacterial Properties Of Coffee Filmmentioning
confidence: 99%
“…In the previous study, the antimicrobial activity of pectin alone was not extensively reported in the literature. However, a report that used citrus pectin in the functional films showed inhibitory effects against L. monocytogenes, E. coli and S. aureus [8,9]. Furthermore, Daoud et al [10] reported that the lyophilized citrus pectin showed activities against 16 clinical isolates and 2 reference strains of Helicobacter pylori.…”
Section: Introductionmentioning
confidence: 99%
“…Pectic polysaccharides are one of the important functional biomaterials with significant antimicrobial activity. The antimicrobial activity application of pectin is demonstrated developing antimicrobial film which is effective against Streptococcus infantarius , L. monocytogenes and E. coli 31 …”
Section: Functional Materials For Antimicrobial Applicationsmentioning
confidence: 99%